VII Salón de Arte Bancomer : Tendencias. - Contreras Ramírez, Verónica; Velásquez Robinson, Gabriela (Cd. de México : Fundación Bancomer, 2001)
Aceves, Franco ; Adelantado, Olga ; Amorales, Carlos ; Alÿs, Francis ; Arce, Marco ; Bonillas, Iñaki ; Brailovsky, Katya ; Brüggemann, Stefan ; Brunet, Fernanda ; Calatayud, Adriana ; Clouthier, Irene ; Cohen, Laura ; de la Macorra, María José ; de la Torre, Jamex ; de la Torre, Einar ; Dellekamp, Marianna ; Echeverria, Alejandra ; Eibenschutz, Galia ; Elizondo, Pía ; García Correa, Fernando ; García Torres, Mario ; Gavaldón, Alfredo ; Glassford, Thomas ; Grimm, Verena ; Gutiérrez, Rubén ; Gutiérrez Yolanda ; Ibañez Cerda, Alberto ; Manterola, Franco ; Matus, Luciano ; Mazal, Ricardo ; Orlaineta, Edgar ; Quezada, Abel ; Ranc, Carlos ; Rodríguez, Sebastián ; Rodríguez, Victor ; Slim, Pedro ; Smith, Melanie ; Ugalde, Fabián ; Velázquez Teresa
boek